A Review of Some Protozoan Parasites Causing Infertility in Farm Animals. (4th December 2013) - Kaltungo, B. Y.; Musa, I. W.
Abstract : The paper reviews some protozoan parasites responsible for infertility in livestock with specific emphasis on neosporosis, sarcocystosis, toxoplasmosis, and trichomoniasis. It highlights the transmission, pathogenesis, clinical signs, diagnosis, prevention, control, and treatment of the individual parasite. It is concluded that these parasites are often overlooked during investigation into causes of abortion in livestock, and they may, however, be responsible for some infertilities in this group of animals which may result in severe economic losses.